Quality of care in cancer: An exploration of patient perspectives - Sandeep Mahapatra; Sukdev Nayak; Sanghamitra Pati (Journal of Family Medicine and Primary Care, 2016)
Introduction: Patient satisfaction is as important as is the care itself. When the patient has a disease like cancer it becomes even more important. A cancer patient not only suffers from the disease but also undergoes substantial mental trauma, agony, stress, uncertainty, and apprehension. There are limited studies in India eliciting patient's views on the quality of care being received by cancer patients. Methodology: A cross-sectional triangulation data transformation model mixed method design (Quant + Qual) was used to conduct the study between March and May 2015 among patients attending specialty hospitals providing oncology services in Odisha, India. The quantitative data were collected using, Patient Satisfaction Questionnaire-18 to assess satisfaction. The qualitative data were obtained through in-depth interviews using open-ended questionnaire. Results: The results showed that general satisfaction among the patients was 60%. The maximum score was obtained for the communication of doctors. The qualitative findings revealed that travel for distant places for minor illness, waiting period, and lack of services at the primary care facilities were reasons for patient's dissatisfaction. Conclusion: The study found that the patients were generally satisfied with the quality of services. However, more studies should be conducted including perceptions of the patients as well as the caregiver.